In Memoriam: Prof. Thomas Hylland Eriksen (1962–2024) - Gordana Gorunović (Etnoantropološki Problemi, 2025)
It is with deep regret that we announce that the distinguished Professor of Anthropology Thomas Hylland Eriksen, a member of our International Editorial Bord, passed away on November 27, 2024 in Oslo.